Who Benefits from U.S. Food Aid? - Visek, Lauren E. (Tufts Archival Research Center, 2005)
Using data on U.S. food aid shipments from 1960-2000, we utilize a regression using instrumental variables and fixed effects by country and commodity in a 2SLS regression. This paper finds the effect changes over time depending on the type of food aid that dominated the evaluated period. The changing effect of food aid contains inherent policy applications and provides a hypothesis as to why the results in the previous literature vary so widely.